Pengaruh Inflasi, Suku Bunga, Nilai Tukar Dan Faktor Internal Perusahaan Terhadap Kinerja Saham Emiten Di Bursa Efek Indonesia - Seprilia Martha Kailuhu; Natelda. R. Timisela (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Fluctuations in inflation, interest rates, and exchange rates are macroeconomic indicators that can affect the performance of issuers' shares on the Indonesia Stock Exchange, especially when linked to internal conditions that vary between sectors. The instability of these macroeconomic variables creates uncertainty for investors and necessitates a more comprehensive study. This study aims to analyze the effect of inflation, interest rates, exchange rates, and internal company factors on the performance of listed companies on the Indonesia Stock Exchange. The study uses a descriptive qualitative approach with a literature review method of 20 national scientific articles and 1 accredited international scientific journal from the period 2022–2025. The data were analyzed through document analysis by comparing and synthesizing the findings of previous studies. The results show that the influence of inflation, interest rates, and exchange rates on stock performance is inconsistent across industry sectors and research periods. Internal company factors, particularly profitability and company size, play an important role in determining stock performance and strengthening issuers' resilience to macroeconomic pressures. Simultaneously, macroeconomic variables and internal company factors interact with each other in influencing the stock performance of issuers on the Indonesia Stock Exchange.